2018
DOI: 10.1021/acs.langmuir.8b03382
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Helical Structures in Systems with Competing Interactions under Cylindrical Confinement

Abstract: The behavior under confinement of nanoparticles interacting with the short-range attraction and long-range repulsion potential is studied by means of Monte Carlo simulations in the grand canonical ensemble. The study is performed at thermodynamic conditions at which a hexagonal cylindrical phase is the most stable phase in bulk. In these conditions, cylindrical confinement promotes the formation of helical structures whose morphology depends upon both the pore radius and boundary conditions. As the pore radius… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 21 publications
(50 reference statements)
2
26
0
1
Order By: Relevance
“…16,17 In our former studies we have shown that pores with circular cross-section induce the formation of helical structures. 11 It has to be stressed that we have never observed structures composed of straight cylindrical clusters (with the exception of a single cylindrical cluster in the center of the pore for some selected pore diameters).…”
Section: Cylindrical Hexagonal Phase Under Confinementmentioning
confidence: 69%
See 2 more Smart Citations
“…16,17 In our former studies we have shown that pores with circular cross-section induce the formation of helical structures. 11 It has to be stressed that we have never observed structures composed of straight cylindrical clusters (with the exception of a single cylindrical cluster in the center of the pore for some selected pore diameters).…”
Section: Cylindrical Hexagonal Phase Under Confinementmentioning
confidence: 69%
“…In addition, we found that the length of the channel plays an important role as the helical structures have a preferred pitch about 8.0s. 11 We need to keep the length of the channels as multiples of the optimal pitch to guarantee the proper formation of helical structures when the geometry of the channels allows it. Thus, the channel length was set to L z = 24s for all the studied geometries in this work.…”
Section: The Model and The Simulation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Does the cylinder confinement enable systems to evolve in a sinusoidal-like manner? Yes, one can learn from fluid dynamics that under specific thermodynamic conditions and considering interacting (nano-)particles with short-range attraction and long-range repulsion, cylindrical confinement promotes the formation of helical structures (Jung & Ha, 2019 ; Serna et al, 2019 ). Their morphology depends on pore size and boundary conditions (Fig.…”
Section: Towards a Conceptual Framework For Analyzing Sustainable Biomentioning
confidence: 99%
“…
Fig. 2 Helical structures; a A single, double, and triple concentric helix in the cylinder confinement (modified from Serna et al, 2019 ); b DNA c Alpha-helix with top and side views; d spiral structures in nature; e spiral structures in food and non-food products; f two propagating sinusoidal curves form a helix; g predator–prey populations in time; h helicoid structure. Source: Fig.
…”
Section: Towards a Conceptual Framework For Analyzing Sustainable Biomentioning
confidence: 99%